2008
DOI: 10.1002/msc.139
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the healthcare journey of patients with rheumatoid arthritis: A mapping project – implications for practice

Abstract: This unique mapping approach used qualitative research and process mapping to compare patient experiences against recognized standards and guidelines. These twenty-two stories reveal important insights into the challenges experienced in negotiating these healthcare journeys and the impact upon the individual as a result of variances in standards of care received. The participants in this study were chiefly self-motivated, informed and articulate, and did not reflect the broad ethnic, social or cultural diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 23 publications
2
58
0
Order By: Relevance
“…Often when people initially sought help, it was not usually for an explanation of the cause of their escalating symptoms or to receive a diagnosis, but instead for symptom relief 27 33 35…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Often when people initially sought help, it was not usually for an explanation of the cause of their escalating symptoms or to receive a diagnosis, but instead for symptom relief 27 33 35…”
Section: Resultsmentioning
confidence: 99%
“…Causal beliefs associated with RA symptoms included stressful life events, child birth, work,27 28 31 4143 an injury or ‘overdoing it’ 2629 3133 35 3941 44. Attributing symptoms to external factors often meant that people believed their symptoms to be temporary, and not requiring medical attention 32 33 35.…”
Section: Resultsmentioning
confidence: 99%
“…37 Studies published to date on patient journeys have been limited, providing data from small numbers of research interviews or focus groups. [21][22][23][24]38 The current study, while limited to 300 respondents, represents the largest published examination of women's journeys with hypertension. Results of the current study reinforce themes observed in other studies of patient journeys with cardiovascular disease, including the need for patientcentric communication 24 and the need for health care providers to understand the social constructs that are unique to women's experiences with cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies mapping other medical journeys (eg, cancer, rheumatoid arthritis, and hearing loss) have provided valuable insight into patient perspectives and key areas for improving clinical management strategies. [20][21][22][23] Data on such journeys through hypertension are limited 24 and this is the first study to explore the processes of the US health care system, specifically examining the experience of highrisk postmenopausal women. Participants were members of the database of WomenHeart: The National Coalition for Women With Heart Disease, which is the only national organization supporting women living with or at risk for cardiovascular disease through advocacy, education, and patient support.…”
mentioning
confidence: 99%
“…Biologic DMARDs are an integral part of the patient's journey and, as such, the assessment, administration, management and monitoring of biologic therapies are an important part of the patient's treatment pathway (Oliver, 2008). The King's Fund and the National Audit Office Reports on the management of RA have identified the value of the nurse specialist role, highlighting the fact that patients value their contribution and wish for continuity of care to be maintained.…”
Section: Biologics: the Role Of The Cnsmentioning
confidence: 99%